EFFECT OF WELDING HEAT INPUT ON THE CORROSION RATE OF CARBON STEEL MMA WELDING - Melvin Bismark H Sitorus (Universitas Mercu Buana, Prodi S2 Teknik Mesin, 2021)
AbstractSteel is one of materials which often used on steel construction, bridge construction, and high rise building construction. Construction using welding joint is expected able to withstand construction loads for a long time. After a while weldment will be exposed to corrosion that will be construction failure in turn. One of the most important parameter in welding is heat input, however it hasn’t obtain correlation between heat input and corrosion rate on MMA (Manual Metal Arch) weldment on mild steel. This paper aims to obtain correlation between heat input and corrosion rate of low carbon steel with MMA welding. The result was show that corrosion rate tend to decrease with adding of duration, where higher corrosion rate at heat input 0,8108 kJ/mm was 68,68 gm/m2 hr at duration 5 hour.